An investigation of plant-derived cardiac glycosides as a possible basis for aposematism in the aphidophagous hoverfly Ischiodon aegryptius (Wiedemann) (Diptera: Syrphidae) - Malcolm, Stephen Baillie (Rhodes University, Faculty of Science, Department of Zoology and Entomology, 1977)
The chemical defences of insects against predators are either passive or aggressive. Passive defence is achieved through crypsis, and aggressive defence is maintained by a conspicuous or 'aposematic' (Poulton, 1890) appearance that advertises some noxious quality of the insect harmful to a predator. Aposematism is mutually beneficial to both the bearer and its predator, whereas crypsis only benefits the prey species. It is therefore not surprising that the fascinating array of chemical defences in insects is both diverse and widespread (Roth and Eisner, 1962). Intro. p. 1.
Keywords: Diptera; Syrphidae; Aphidophagous insects; Predatory animals; Insect-plant relationships; Insect pests -- Biological control; Insects as carriers of disease